Antiproliferative activity of Larrea divaricata Cav. on Lymphoma cell line: Participation of hydrogen peroxide in its action proliferation - Davicino, Roberto Carlos (2010)
Larrea divaricata is a plant used in Argentina. The aim was to analyze the participation of H2O2 in the antiproliferative effect of L divaricata on BW5147 cells. Different studies were performed: proliferation, viability, nitrite production, apoptosis, oxygen reducing activity, NF-κ B translocation, H2O2 production, H2O 2 scavenging activity, and effect on exogenous superoxide dismutase. The extract decreased proliferation and induced apoptosis through P-38 and ERK pathways. The extract activated Mn2+-SOD, increasing H 2O2, which was implicated in the antiproliferative mechanism by the increase of Nitric oxide (NO). New drugs, which can increase H2O2, could be a therapeutic strategy for the treatment of cancer.